NX210c drug candidate peptide strengthens mouse and human blood-brain barriers - Campbell, Matthew (My University, 2024)
Background: Alterations of blood-brain barrier (BBB) and blood-spinal cord barrier have been documented in various animal models of neurodegenerative diseases and in patients. Correlations of these alterations with functional deficits suggest that repairing barriers integrity may represent a disease-modifying approach to prevent neuroinflammation and neurodegeneration induced by the extravasation of blood components into the parenchyma. Here, we screened the effect of a subcommissural organ-spondin-derived peptide (NX210c), known to promote functional recovery in several models of neurological disorders, on BBB integrity in vitro and in vivo. Methods: In vitro, bEnd.3 endothelial cell (EC) monolayers and two different primary human BBB models containing EC, astrocytes and pericytes, in static and microfluidic conditions, were treated with NX210c (1-100 μM), or its vehicle, for 4 h and up to 5 days. Tight junction (TJ) protein levels, permeability to dextrans and transendothelial electrical resistance (TEER) were evaluated. In vivo, young and old mice (3- and 21-month-old, respectively) were treated daily intraperitoneally with NX210c at 10 mg/kg or its vehicle for 5 days and their brains collected at day 6 to measure TJ protein levels by immunohistochemistry. Results: NX210c induced an increase in claudin-5 protein expression after 24-h and 72-h treatments in mouse EC. Occludin level was also increased after a 24-h treatment. Accordingly, NX210c decreased by half the permeability of EC to a 40-kDa FITC-dextran and increased TEER. In the human static BBB model, NX210c increased by ∼ 25% the TEER from 3 to 5 days. NX210c also increased TEER in the human 3D dynamic BBB model after 4 h, which was associated with a reduced permeability to a 4-kDa FITC-dextran. In line with in vitro results, after only 5 days of daily treatments in mice, NX210c restored aging-induced reduction of claudin-5 and occludin levels in the hippocampus, and also in the cortex for occludin. Conclusions: In summary, we have gathered preclinical data showing the capacity of NX210c to strengthen BBB integrity. Through this property, NX210c holds great promises of being a disease-modifying treatment for several neurological disorders with high unmet medical needs.
PUBLISHED
cited By 0
Keywords: BBB leakage; BBB repair; SCO-spondin-derived peptide; Treatment